Effect of Acupuncture on Post-implant Paresthesia - Crischina Branco Marques Sant'Anna; Paulo Renato Junqueira Zuim; Daniela Atili Brandini; Aimée Maria Guiotti; Joao Batista Vieira; Karina Helga Leal Turcio (Medical Association of Pharmacopuncture Institute, 2017)
Paresthesia is defined as an alteration in local sensibility, associated with numbness, tingling, or unpleasant sensations caused by nerve lesions or irritation. It can be temporary or permanent. The treatment protocol for facial paresthesia is primarily based on the use of drugs and implant removal, which may not be completely effective or may require other risk exposure when there is no spontaneous regression. However, other therapeutic modalities such as acupuncture can be used. The aim of this study is to report a case of a patient with paresthesia of the inferior alveolar nerve and pain caused by an implant surgery performed 2 years earlier. The patient received acupuncture treatment during 4 months of weekly sessions. Six points were used: Large Intestine (LI4), Large Intestine (LI11), Stomach (ST36), Liver (LR3), Extra Head and Neck (E-HN-18), and Stomach (ST5). The visual analog scale was used before and after each session for the analysis of paresthesia and pain, together with assessment of the paresthesia by delimitation of the desensitized region of the skin and presented discomfort. Pain remission and reduction in the size of the paresthesia area occurred after four sessions.